Nitrification and mineralization potentials in a limed Ultisol in the humid tropics - Arora , Y.; Mulongoy, K.; Juo, A.S.R. (1986)
We studied the effect of liming on the rates of mineralization and nitrification in a coarse-textured kaolinitic Ultisol. Soil samples were taken from field plots which received lime rates from 0 to 4mt/ha three years prior to the study. The pH of the soil samples varied from 4.2 to 6.1.